I survived : the Joplin tornado, 2011 - Tarshis, Lauren (Tarshis, Lauren. I survived., 2015)
In 2011, eleven year old Dexter is thrilled to have the opportunity to go storm chasing with Dr. Norman Gage, but when the tornado they are following changes direction, Dexter's bravery is about to be tested.